Evaluation of the influence of surface preparation on the performance of anticorrosive paint by salt spray test - Paucar Cuba, Karin (2007)
The following article presents the results of performance evaluation systems anticorrosive paint for use in the national industry, epoxy systems, using the accelerated salt spray (fog) test(ASTM B 117). The experiment was carried out for a period of exposure 125 days or 3000hours. The paint systems were tested applied on steel plates with different types of surfacepreparation: manual, mechanical and sandblasted (white, dry and wet). The evaluation ofthe samples tested were made according to the criteria of the relevant standards: Grade Oxidation, Blistering and Deterioration in Incision. The degree of deterioration in the incision showed that the epoxy systems with sandblasting surface preparation show a greater resistance to deterioration in the incision, compared to those of surface preparation manual cleaning and mechanical cleaning.